The Relationship Between Students’ Perception of Lecturers’ Sense of Humor and Learning Motivation Among Students at UIN Ar-Raniry Banda Aceh - Fahrozi, Muhammad Erwin; Barmawi, Barmawi; Zain, Fajran (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Learning motivation refers to the overall driving force within students that initiates, sustains, and directs learning activities, ensuring the continuity of the learning process and guiding it toward achieving desired goals. According to Sadirman (2013), learning motivation plays an important role in determining the rise and fall of academic performance. This study aims to examine the relationship between students’ learning motivation and lecturers’ sense of humor among students at UIN Ar-Raniry Banda Aceh. The instruments used in this study were the Lecturers’ Sense of Humor Scale, developed based on the theory of Thorson and Powell (1997), and the Learning Motivation Scale, developed based on the theory of Santrock (2004). The research employed a quantitative approach with a correlational method, and sampling was conducted using the stratified random sampling technique. The total sample consisted of 348 students. The results showed a correlation coefficient (r) = 0.259 with a significance value (p) = 0.000, indicating a significant positive relationship between students’ learning motivation and lecturers’ sense of humor at UIN Ar-Raniry Banda Aceh. This means that the higher the lecturers’ sense of humor, the higher the students’ learning motivation, and conversely, the lower the lecturers’ sense of humor, the lower the students’ learning motivation.